2018
DOI: 10.1038/s41598-018-34093-4
|View full text |Cite
|
Sign up to set email alerts
|

Ptf1a inactivation in adult pancreatic acinar cells causes apoptosis through activation of the endoplasmic reticulum stress pathway

Abstract: Pancreas transcription factor 1 subunit alpha (PTF1A) is one of the key regulators in pancreatogenesis. In adults, it transcribes digestive enzymes, but its other functions remain largely unknown. Recent conditional knockout studies using Ptf1aCreER/floxed heterozygous mouse models have found PTF1A contributes to the identity maintenance of acinar cells and prevents tumorigenesis caused by the oncogenic gene Kras. However, Ptf1a heterozygote is known to behave differently from homozygote. To elucidate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Instead, Pdx1-inactivated b cells lose their b cell identity either by losing pancreatic hormone expression or transdifferentiation to glucagon-expressing cells [32]. On the other hand, we previously reported that Ptf1a inactivation in adult acinar cells causes rapid and severe apoptosis via ER stress and a reduction in organ size, mostly due to cell apoptosis but also in exceptional cases transdifferentiation to duct cell type [14]. In the present study, we found that Pdx1-depleted acinar cells do not show apparent apoptosis or transdifferentiation to other cell types, but instead become senescent.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Instead, Pdx1-inactivated b cells lose their b cell identity either by losing pancreatic hormone expression or transdifferentiation to glucagon-expressing cells [32]. On the other hand, we previously reported that Ptf1a inactivation in adult acinar cells causes rapid and severe apoptosis via ER stress and a reduction in organ size, mostly due to cell apoptosis but also in exceptional cases transdifferentiation to duct cell type [14]. In the present study, we found that Pdx1-depleted acinar cells do not show apparent apoptosis or transdifferentiation to other cell types, but instead become senescent.…”
Section: Discussionmentioning
confidence: 97%
“…All tissue preparation was performed with cardiac perfusion fixation as previously described . Briefly, after anesthetizing the mice, we infused wash solution (0.1 m phosphate buffer containing 5 m m EGTA, 2 m m MgCl 2 and 0.9% NaCl) into the left ventricle for 1 min to wash out blood and then infused fixation solution (0.1 m phosphate buffer containing 2 m m MgCl 2, 5 m m EGTA, 4% paraformaldehyde, 2% glutaraldehyde and 30% sucrose) for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune cell infiltration, along with chemokine and cytokine cascade-mediated inflammation, plays a critical role in the development of this disease[ 15 , 16 ]. Although increasing evidence shows that inhibiting the immune cells (neutrophils) or specific adhesion molecules (P-selectin, lymphocyte function antigen-1, and CD11a/CD18) may have a therapeutic effect on excessive inflammatory responses in AP[ 17 - 20 ], no drug that effectively modulates the outcome of AP has been identified[ 21 ]. It is urgent to find a novel therapeutic target for the treatment of AP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ptf1a dosage experiments from the homozygous-to-null status done using conditional Ptf1a KO mice, showed pancreatic hypoplasia and glucose intolerance in a dosage-dependent manner (Fukuda et al, 2008). In addition, it was shown that Ptf1a null acinar cells have enhanced ER stress and accelerated apoptosis evidenced by increased PERK, eIF2, ATF4 and ATF6 pathways, suppression of the IRE1 pathways and increased CHOP levels, leading to reduced pancreatic size (Sakikubo et al, 2018). The authors proposed that the shift in cellular identity (acinar to ductal-like) may be a compensatory response to promote cell survival.…”
Section: Molecular Phenotypementioning
confidence: 99%